A invalidação das licenças urbanísticas pela administração pública e o devido processo legal - Botrel, Karla (2009)
The goal of the present work is to study the reflexes of the due process of law on the public administration decisions referring to urban licenses declaration of invalidity. Therefore, the dissertation analyzes the power of the public administration to impose limits to individual property and freedom, the concept and the essential aspects of urban licenses, the due process of law, its historical evolution, its contemporary concept and applicability in the ambits of public administration and administrative processes, comprehending also the declaration of invalidity of the urban licenses and its consequences, such as the possible limits to the juridical duty of the public administration of controlling its own acts legality. The conclusion drawn from this research was that the observation of the due process of law in its two aspects, material and formal, in administrative processes for declaration of invalidity of urban licenses serves as a guideline to the public administration when defining, in the concrete cases, the most adequate behavior in order to achieve public interest and maintain the stability of the juridical system, which can be done through the effective declaration of invalidity of the administrative act or, eventually, through the stabilization of the legal situation and refrain from declarating its invalidity in recognition of other juridical principles concretely present in the case, such as legal certainty and good faith